Instant hands-on testing with PHPUnit how-to : a practical guide to getting started with PHPUnit to improve code quality - Lively, Mike (Packt Publishing, 2013)
Filled with practical, step-by-step instructions and clear explanations for the most important and useful tasks. This is a Packt Instant How-to guide, which provides concise and clear recipes for getting started with PHPUnit for performing code testing and improving code quality.""Instant Hands-on Testing with PHPUnit How-to"" is for PHP developers that have an appreciation for writing accurate code. If you are new to PHPUnit, it will give you a solid foundation for understanding how to use PHPUnit to write tests for your projects. If you already have a cursory understanding of PHPUnit it will.